6x+10=8x-2

Simple and best practice solution for 6x+10=8x-2 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6x+10=8x-2 equation:


Simplifying
6x + 10 = 8x + -2

Reorder the terms:
10 + 6x = 8x + -2

Reorder the terms:
10 + 6x = -2 + 8x

Solving
10 + 6x = -2 + 8x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-8x' to each side of the equation.
10 + 6x + -8x = -2 + 8x + -8x

Combine like terms: 6x + -8x = -2x
10 + -2x = -2 + 8x + -8x

Combine like terms: 8x + -8x = 0
10 + -2x = -2 + 0
10 + -2x = -2

Add '-10' to each side of the equation.
10 + -10 + -2x = -2 + -10

Combine like terms: 10 + -10 = 0
0 + -2x = -2 + -10
-2x = -2 + -10

Combine like terms: -2 + -10 = -12
-2x = -12

Divide each side by '-2'.
x = 6

Simplifying
x = 6

See similar equations:

| log(x-10)=2-(log(x-1)) | | -3d+4=-2d+10 | | log(x-10)=2-log(x-1) | | 6w-(7x-2w)+4= | | 2d+3=8+d | | 2d+3=32 | | 3p-2=100 | | 3/x-12=x-4 | | 2(1x+4)=30 | | ln(2a)=0 | | x^2+2x-1=5x+3 | | -(-2w-x)+4(-6x-5w)= | | 2x+3=5-2 | | 3x/12=6 | | -x/4-5=7 | | C/3+4=-1 | | 5m+27+4m=72 | | 4-a/8=-3 | | log(x)+log(x+5)=log(x+4) | | 4-8m= | | 2(x+7)=10-2x+3 | | 2(x+7)=-8+28+2x | | 1.6(x-2.8)=(0.2+1.5)-0.7 | | 2(x+7)=-8+22+2x | | x^2-4x+1=x | | 30v=22+80v | | 100=200-3a | | 100=200-5a | | 8x-(6x+12)=50 | | 5x^2-50*x+90=10 | | 4(5x-1)+3(1-7x)= | | 4x^2+44x+112=280 |

Equations solver categories